(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
While the main goal of education is to form the basis of a comprehensively developed personality, now the main focus is on educating an active, creative person who is aware of the global problems of mankind, ready to participate in solving them. as much as possible. Now we need people who do not think in stereotypes, but are able to find new ways to solve the problems, to find a way out of the problem. More recently, all children have come to believe that they are intellectually and emotionally equal. You just have to teach them to think, to empathize, to solve complex logical problems. However, modern educational experience shows that there are differences between children. Children are more developed than their peers in intelligence, creative ability, the ability to classify, generalize, and find relationships. They are always looking for answers to their questions, they are inquisitive, independent, active. Early identification, training and education of gifted and talented children is one of the key challenges in improving the education system